Transcriptome analysis reveals key defense genes associated with resistance to banana blood disease - Thanwanit Thanyasiriwat; Aphidech Sangdee; Ladawan Rattanapolsan; Praphat Kawicha; Araya Arjcharoen Theanhom; Ratri Boonruangrod; Pumipat Tongyoo (BMC Genomics, 2025)
Abstract Background Bananas are a globally significant crop, but their production is threatened by banana blood disease (BBD), caused by Ralstonia syzygii subsp. celebesensis (Rsc). While resistant cultivars like ‘Khai Pra Ta Bong’ (AAA genome) have been identified, the genetic basis of resistance remains unclear. This study uses RNA sequencing (RNA-seq) to investigate gene expression changes in ‘Khai Pra Ta Bong’ over seven days post-infection with Rsc isolate MY4101. Candidate genes associated with resistance were also evaluated in other cultivars, including resistant, moderately resistant, and highly susceptible cultivars. Results RNA-seq analysis identified several genes associated with BBD resistance mechanisms, showing significant upregulation as early as 12 h post-inoculation. Key molecular processes, including xyloglucan endotransglucosylase hydrolases, receptor-like kinases, and glycine-rich proteins, were enriched at 24 h post-inoculation, highlighting the activation of effector-triggered immunity (ETI). Quantitative real-time RT-PCR (qRT-PCR) validation further confirmed the differential expression of several key defense-related genes in other banana cultivars. Conclusions The study highlights the potential of these differentially expressed genes as genetic markers for BBD resistance, which could be valuable for breeding programs aimed at enhancing resistance in banana cultivars. These findings provide important insights into the molecular mechanisms of disease resistance and contribute to developing more efficient strategies for sustainable banana production and global food security.